ANALYSIS OF NUTRITION SOCCER ACADEMY (MMA) PLAYERS IN MATARAM - Balkis Ratu NL Esser; Indri Susilawati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2020)
The background of this research is nutrition is one of the factors that support a good level of achievement, but many sports players do not realize the importance of nutrition in sports activities. The purpose of this study is to determine the nutritional status of the players of Mataram Soccer Academy (MSA) by first knowing the IMT (Body mass index) The research method used was quantitative descriptive. The sample of this study was 60 Mataram Soccer Academy (MSA) players with purposive sampling technique. Variables in this study are the Body Mass Index of the Mataram Soccer Academy (MSA) players. Instrument weight tests using digital scales, height using microtoa, both of these tools are used to get weight data and height of each player or anthropometric data so that the nutritional status of each player can be known. Data Analysis Techniques are performed by The results of the average study for nutritional status based on the IMT value of Mataram Soccer Academy (MSA) players showed that included in the obesity category amounted to 1 person with a percentage of 1.67%, in the fat category numbered 5 people with a percentage of 8.33%, in the category normal, the thin category is 3 people with a percentage of 5%, and the very thin category is 1 person with a percentage of 1.67%. So the conclusion is that most Mataram Soccer Academy (MSA) players are in the normal category with a percentage of 83.33%. The conclusions of this study are 1) the nutritional status of Mataram Soccer Academy (MSA) players based on normal BMI. The recommendations for this research are to provide an understanding of coaches, coaches, parents and players to always pay attention to sports nutrition and make nutritional status as a reference to position players and pay attention the level of nutrition and energy related to the player's condition.